Effect of In and Cd co-doping on the thermoelectric properties of Sn1−xPbxTe - Subhajit Roychowdhury; Kanishka Biswas (Materials Research Express, 2019)
Pristine tin telluride (SnTe) with a similar electronic structure to PbTe shows inferior thermoelectric performance owing to high p -type hole concentration (10 ^21 cm ^−3 ), high lattice thermal conductivity, κ _latt (∼2.8 W mK ^−1 at room temperature) and large energy gap between light and heavy hole valence bands. Interestingly, 30 mol% substitution of lead in SnTe decreases the excess hole carrier concentration and lattice thermal conductivity (∼0.67 W m ^−1 K ^−1 at 300 K) significantly. Here, we report the promising thermoelectric performance in Sn _0.70 Pb _0.30 Te by enhancing the Seebeck coefficient via the co-adjuvant effect of resonant level formation and valence band convergence. We obtain a Seebeck coefficient value of ∼141 μ V K ^−1 at 300 K, which further increases to ∼260 μ V K ^−1 at 708 K for Sn _0.70 Pb _0.30 Te—3% Cd and 0.50% In sample. This is one of the highest S values for SnTe based system, to the best of our knowledge. In and Cd have discrete but complementary roles to augment the Seebeck coefficient value of Sn _0.70 Pb _0.30 Te where In acts as a resonant dopant and Cd serves as valence band convergent, respectively, as demonstrated by the well-known Pisarenko plot of SnTe. Finally, we have achieved a maximum thermoelectric figure of merit, zT, of ∼0.82 at 654 K for Sn _0.70 Pb _0.30 Te—3% Cd and 0.25% In sample.